PENTECOSTALISMO BRASILEIRO DE IMIGRAÇÃO: CONTEXTO, COTIDIANO E INSTITUCIONALIZAÇÃO DA CONVENÇÃO DAS IGREJAS BATISTAS INDEPENDENTES - VALÉRIO, SAMUEL PEREIRA (2019)
The present research investigates the Brazilian Pentecostalism of immigration that arrived at Brazil founding the Baptist Church Swedish (IBS) and, later, the Convention of the Independent Baptist Churches (CIBI). Among at the main specificities of that church are the transformation of the charism, its ethnicity, cultural preservation as a form of cohesion of the group, being a bureaucratic and rational church, a trait inherited from Örebromissionen (ÖM), that is, Örebro Mission. Starting from the investigation of historical documents and empirical data collection – primary sources –, in addition to studies on the origin and foundation of the IBS, the present research exposes the origins, the history of this denomination, analyzing disputes for power among the Swedish missionaries and the native shepherds, as well as their logical form of functioning. The search for the denominational rise of indigenous pastors is a determining factor in the identity construction of what became the nationalization of IBS through the birth of CIBI. Joints and power games were developed during the first forty years of mission in Brazil. The most recent features of the denomination as well as its present structures were also analyzed in this research, in order to understand how, over the years, a doctrinal ambiguity and a fragmented theology was possible, as a result of the reception of ministers from other evangelical denominations, especially Pentecostals. The CIBI is a centenarian Pentecostalism that ran to the margin of the other Pentecostal denominations founders of the movement in the country, having a very specific and unique way of acting. Max Weber's typologies of power, Foucault's power-building structure and Pierre Bourdieu's field concept provide the theoretical arsenal for the analysis of the history and religious practice of IBS and subsequently CIBI. It should be noted that CIBI is a centennial Pentecostal convention not cataloged by researchers of the Pentecostal religious phenomenon.